Effects of Benzyladenine, Watering Frequency and Duration of Shading on Growth and Quality of Dracaena Sanderiana and Codiaeum Variegatum - Fuadi, Misril (2004)
This study was carried out with the main objective of looking at the effects of benzyladenine (BA), frequency of watering and duration of shading with various acclimatization techniques on growth and quality retention of Dracaena sanderiana and Codiaeum variegatum during subsequent shipping conditions. This study comprised three experiments. The first experiment was designed to evaluate the effect of BA as foliar application on Dracaena sanderiana and Codiaeum variegatum. Concentrations of BA applied were 0 (control), 75, 150, 225 and 300 mgL-1. The second experiment was designed to evaluated the effect of different concentrations of BA at 0 (control), 75, 150, 225 and 300 mgL-1 and frequency of watering daily, every 4, 7 and 10 days on Dracaena sanderiana and Codiaeum variegatum. A third experiment was conducted to evaluate the effect of the selected BA concentrations (control and 225 mgL-1 for Dracaena sanderiana and 150 mgL-1 for Codiaeum variegatum) and in combination with duration of shading (2, 4 and 6 weeks) subsequent shipping condition. iv For Dracaena sanderiana and Codiaeum variegatum, growth and plant quality in terms of photosynthesis rate, stomatal conductance, chlorophyll content, plant height and plant grade were significantly (p<0.05) affected by BA. For Dracaena sanderiana, the photosynthesis rate (6.74 molm-2s-1) and chlorophyll content were the highest when sprayed with 300 mgL-1 BA, while (5.40 molm-2s-1) for Codiaeum variegatum at 150 mgL-1 BA. As expected, photosynthesis rate increased with the chlorophyll content. The photosynthesis rate is more than double with this treatment compared to other treatments. Stomatal conductance, leaf fresh weight and plant grade were also significantly (p<0.05) affected with different concentrations of BA. Similar to the photosynthesis and chlorophyll content of Dracaena sanderiana, plants sprayed with 300 mgL-1 BA gave a better growth response, and the requirement of Codiaeum variegatum needs lower concentrations (150 mgL-1 BA). In order to obtain a good plant grade in term of leaf freshness, Dracaena sanderiana and Codiaeum variegatum required BA concentration of 300 mgL-1 (4.50 = excellent quality) and 150 mgL-1 (4.17 = excellent quality), respectively. A good quality plant seems to be closely related to photosynthesis rate of the leaf. Interaction between BA concentration and frequency of watering gave satisfactory results. This interaction resulted in the highest chlorophyll content at BA 225 mgL-1 and frequency of watering every 4 days for Dracaena sanderiana. The same interaction also produced high grade of Dracaena sanderiana and Codiaeum variegatum plant. No significant interaction between BA concentrations and frequency of watering was observed on photosynthesis rates, stomatal conductance, specific leaf area, fresh and dry weight parameters. For Dracaena sanderiana, the optimum photosynthesis rate (5.87 molm-2s-1) v occurred with BA concentration of 187.50 mgL-1 and photosynthesis rate decreased with an increased frequency of watering. For Codiaeum variegatum, the optimum photosynthesis rate was found at 3.81 molm-2s-1 with BA concentration of 183.33 mgL-1 and was not significant with frequency of watering. The highest stomatal conductance (1.39 mmolm-2s-1) of Dracaena sanderiana was obtained with BA concentration of 225 mgL-1, stomatal conductance parameter independently was found with BA concentration of 225 mgL-1.The frequency of watering every four days gave the best photosynthesis rate and plant height for Dracaena sanderiana, but no significant response for Codiaeum variegatum.There was a significant interaction between BA concentration and duration of shading on chlorophyll content, plant height increment and plant grade of Dracaena sanderiana. Dracaena sanderiana duration of shaded in the glass house adaptation for six weeks showed the best quality. It is indicated by the highest plant grade (4.50 = excellent quality), the lowest leaf drop and moderate plant height increment, while Codiaeum variegatum occurred with adaptation period for 4 weeks under subsequently simulated shipping condition.